THE INFLUENCE OF LIVE STREAMING AND PRICE DISCOUNT ON IMPULSE BUYING AMONG TIKTOK SHOP USERS THROUGH POSITIVE EMOTION AS AN INTERVENING VARIABLE - Shulha Afifah Azzahra; Ditiya Himawati; Septi Mariani Tis’a Ramadhani; Lies Handrijaningsih (Jurnal Ilmiah Ekonomi Bisnis, 2026)
In the era of globalization, technology and the internet are developing very rapidly. So the internet plays an important role as a means of entertainment, information sources, social media, and business. As the use of social media and digital interactions increases, a new form of online commerce known as social commerce has emerged. This research aim to determine and analyze the effect of live streaming and price discounts on impulse buying in TikTok Shop users through positive emotions as an intervening variable. This research uses primary data obtained through distributing the questionnaires to 150 respondents. The respondents are TikTok Shop users who are over 17 years old and reside in the Greater Jakarta area. This research uses PLS-SEM analysis, which consist of a measurement model (outer model), a structural model (inner model), and a model goodness-of-fit test (model fit). The results of this research show that live streaming and price discounts positive influence impulse buying in TikTok Shop users both directly and indirectly through positive emotions and the variable that has the most dominant influence on impulse buying through positive emotions is price discount.